2019
DOI: 10.1111/1468-5973.12260
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making in multi‐agency groups at simulated major incident emergencies: In situ analysis of adherence to UK doctrine

Abstract: When major incident emergencies occur in the UK (e.g., a terrorist attack), senior representatives convene from local emergency services, civil resource organizations, health agencies, and government. These groups make decisions that minimize the societal and economic impacts of major incidents. Their adherence to UK doctrine was assessed using video footage of 18 groups responding to a major incident in a simulation suite, and six groups responding to a large-scale exercise. There were marked between-group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In contrast, findings of the current study show a tendency for responders to revert to gathering information rather than progressing through stages to take action. These findings parallel Wilkinson et al (2019), who also observed some multiagency strategic groups engaging in redundant deliberation. Similar patterns of decision delay and inertia have also been observed in real incidents (Kerslake, 2018;Pollock, 2013) and have been highlighted in interviews with emergency responders (Power & Alison, 2017).…”
Section: Sequence Of Decision Phasessupporting
confidence: 80%
See 4 more Smart Citations
“…In contrast, findings of the current study show a tendency for responders to revert to gathering information rather than progressing through stages to take action. These findings parallel Wilkinson et al (2019), who also observed some multiagency strategic groups engaging in redundant deliberation. Similar patterns of decision delay and inertia have also been observed in real incidents (Kerslake, 2018;Pollock, 2013) and have been highlighted in interviews with emergency responders (Power & Alison, 2017).…”
Section: Sequence Of Decision Phasessupporting
confidence: 80%
“…There was also evidence of this in TCGs, albeit to a lesser extent. Previous research shows a similar pattern of individual decision-makers taking action without explicitly planning at both operational Klein, 1993Klein, , 2008 and strategic levels (Wilkinson et al, 2019) in extreme environments. Current findings advance on this previous research by examining whether the implementation of the JDM has led to any changes.…”
Section: Sequence Of Decision Phasesmentioning
confidence: 53%
See 3 more Smart Citations